2021
DOI: 10.3390/soc11030071
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Working Conditions, Employment, Career Development and Well-Being of Refugee Researchers

Abstract: The ongoing ‘refugee crisis’ of the past years has led to the migration of refugee researchers (RRs) to European countries. Due to the COVID-19 pandemic, RRs often had to work from home and/or to continue their social, cultural and economic integration process under new conditions. An online survey carried out to explore the impact of the pandemic on the refugee researchers showed that RRs found it difficult to adapt their everyday working life to the ‘home’ setting. The majority have had neither a suitable wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…On the other hand, foreign researchers that migrated to Europe found it difficult to adjust to telecommuting, due to unsuitable working environments and deficient technological equipment [118]. Their worry was focused on their susceptibility regarding precarious contracts and bureaucratic asylum methods, even though they were pleased with public authorities' measures [118]. The authors concluded that most academic researchers did not face a change in their income in contrast to their unemployment ratio.…”
Section: Remote Working and Self Employmentmentioning
confidence: 99%
“…On the other hand, foreign researchers that migrated to Europe found it difficult to adjust to telecommuting, due to unsuitable working environments and deficient technological equipment [118]. Their worry was focused on their susceptibility regarding precarious contracts and bureaucratic asylum methods, even though they were pleased with public authorities' measures [118]. The authors concluded that most academic researchers did not face a change in their income in contrast to their unemployment ratio.…”
Section: Remote Working and Self Employmentmentioning
confidence: 99%
“…Employees who were engaged devoted themselves to work tasks and activities to a greater extent, feeling an added responsibility to work more intensively and be of service to the organization in these sudden and unexpected circumstances. According to research, engaged employees worked longer and harder while working remotely (Lonska et al, 2021;Tzoraki et al, 2021), increasing the risk of burnout syndrome or work-life conflict. Employees who work remotely face an additional challenge in that they do not have direct contact with the organization or their colleagues, which leads to feelings of isolation, loneliness, less importance, and belonging (De-la-Calle-Durán & Rodrguez-Sánchez, 2021).…”
Section: Research Background: the Impact Of Digital Technologies On E...mentioning
confidence: 99%
“…O. Tzoraki (2021) studied the effect of the COVID-19 pandemic analyzing the functioning circumstances, business, vocation advancement, and prosperity of exile specialists and observed that adjusting their regular working life to the 'home' setting is testing. The greater part has had neither a reasonable workplace at home nor the fitting innovation.…”
Section: Literature Reviewmentioning
confidence: 99%